2006
DOI: 10.1016/j.brainresbull.2005.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Visual responses and afferent connections of the n. ventrolateralis thalami (VLT) in the pigeon (Columba livia)

Abstract: The nucleus ventrolateralis thalami (VLT) in pigeons receives direct retinal and forebrain projections and has reciprocal connections with the optic tectum. Although VLT is a component of the avian visual system, no study directly examined its connections or its cellular response characteristics. We, therefore, recorded from single units in the pigeon's VLT while visually stimulating the ipsi-and/or contralateral eye. In addition, tracing experiments were conducted to investigate its afferent connections. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In both species a small to moderate number of neurons from the nucleus subrotundus and the thalamic ventrolateral nucleus project to SL (present data, Atoji and Wild,2004). However, in another study, there is no indication of thalamic ventrolateral nucleus neurons projecting to the septum in the pigeon (Schulte et al,2006).…”
Section: Discussionmentioning
confidence: 97%
“…In both species a small to moderate number of neurons from the nucleus subrotundus and the thalamic ventrolateral nucleus project to SL (present data, Atoji and Wild,2004). However, in another study, there is no indication of thalamic ventrolateral nucleus neurons projecting to the septum in the pigeon (Schulte et al,2006).…”
Section: Discussionmentioning
confidence: 97%
“…Males in the CSB and ASB‐F groups also exhibited an increase in FOS expression in the visual part of the VLT, a poorly studied thalamic nucleus in birds. This nucleus appears to be involved in the integration of visual information as suggested by an electrophysiological study demonstrating the presence of evoked potentials in this nucleus following 500 ms uni‐lateral or bi‐lateral photic stimulation (Schulte et al ., 2004) and indicated by the existence of a massive projection from the visual Wulst, a major visual component of the avian thalamofugal pathway, to the VLT (Schulte et al ., 2004). Moreover, previous tracing studies have identified in quail the existence of projections from the POM to the VLT (Balthazart et al ., 1994) and from the HA to the POM (Balthazart & Absil, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…7B-D, 8B) which, as in other birds, first appears at the rostral margin of the thalamus and continues to form an envelope around the LA (G€ unt€ urk€ un and Karten, 1991), and more caudally around the n. rotundus (Rt) just below the DLL. In the n. ventrolateralis thalami (VLT), which lies between the GLv and Rt and is a known retinorecipient region in birds (Schulte et al, 2006), we found only a few sparse terminals (Fig. 7D).…”
Section: Ventral Thalamusmentioning
confidence: 95%